At-Tadakhulaat As-Shautiyaa min Lughati Al-um ilaa Lughati Al-Arabiya - Hindun, Hindun; Muayyanah, Muayyanah (STAI Syaichona Moh. Cholil Bangkalan, 2023)
Language is one of the most important tools for communication between individuals in daily life and for people to express their feelings. A person needs languages, and at least he has two languages. These phenomena, which are called phonetic interventions or migrations, lead to the corruption of the second language and the language that will be studied. Our Sheikh Muhammad Khalil Islamic University of Bengkalan is the only university that has an Arabic language department and has students from all over Indonesia, most of whom are Madureans. In this case, the researcher wanted to search for clarification of the phonetic migrations from the mother tongue to the Arabic language and its forms. The approach used in this research is a descriptive study. And one of the most important results of this research is that phonetic transmigrations have two forms, or two types, meaning the silent and the vowel. As for the silent, such as replacing the letter with another letter, shortening the long vowels, extending the short, and removing the alphabet out of place, As for the vowels, it is the introduction of dialects that are not suitable for the Arabic language and the introduction of the hamza letters, or it can be It is tilted in the opening movements or stresses before the end of the word.